Qualitative and Quantitative Educational Disparities and Brain Signatures in Healthy Aging and Dementia Across Global Settings - Garcia-Serrano, A (Elsevier Ltd, 2025)
Background: While education is crucial for brain health, evidence mainly relies on individual measures of years of education (YoE), neglecting education quality (EQ). The effect of YoE and EQ on aging and dementia has not been compared. Methods: We conducted a cross-sectional assessment of the effect of EQ and YoE on brain health in 7533 subjects from 20 countries, including healthy controls (HCs), Alzheimer s disease (AD), and frontotemporal lobar degeneration (FTLD). EQ was based on country-level quality indicators provided by the programme for international student assessment (PISA). After applying neuroimage harmonization, we examined its effect, along with YoE, on gray matter volume and functional connectivity. Regression models were adjusted for age, sex, and cognition, controlling for multiple comparisons. The influence of image quality was assessed through sensitivity analysis. Data collection was conducted between June 1 and October 30, 2024. Findings: Less EQ and YoE were associated with brain alterations across groups. However, EQ had a stronger influence, mainly targeting the critical areas of each condition. At the whole-brain level, EQ influenced volume (HCs: Δmean = 2·0 [1·9–2·0] × 10−2, p < 10−5; AD: Δmean = 0·1 [−0·0 to 0·3] × 10−2, p = 0·18; FTLD: Δmean = 3·5 [3·0–4·0] × 10−2, p < 10−5; all with 95% confidence intervals) and networks (HCs: Δmean = 13·5 [13·2–13·7] × 10−2, p < 10−5; AD: Δmean = 5·9 [5·2–6·7] × 10−2, p < 10−5; FTLD: Δmean = 13·2 [11·2–13·7] × 10−2, p < 10−5) 1·3 to 7·0 times more than YoE. These effects remain robust despite variations in income and socioeconomic factors at country and individual levels. Interpretation: The results support the need to incorporate education quality into studying and improving brain health, underscoring the importance of country-level measures. Funding: Multi-partner consortium to expand dementia research in Latin America (ReDLat). © 2025 The Author(s)